1996
DOI: 10.1111/j.1476-5381.1996.tb15778.x
|View full text |Cite
|
Sign up to set email alerts
|

Ligustrazine‐induced endothelium‐dependent relaxation in pulmonary arteries via an NO‐mediated and exogenous L‐arginine‐dependent mechanism

Abstract: St Thomas' Campus, London SEl 7EH 1 Ligustrazine (tetramethylpyrazine, TMP) is a vasodilator that has been reported to have pulmonary selective properties in vivo, but not in vitro. Although TMP is generally described as being endotheliumindependent, we provide evidence here that TMP may have an endothelium-dependent and nitric oxide (NO)-mediated mechanism in pulmonary arteries that could predominate at concentrations used therapeutically in China. Similar effects were seen in small arteries. L-Arginine had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 19 publications
5
28
0
Order By: Relevance
“…It was noticeable that in small arteries the maximum relaxation to isoprenaline was signi®cantly less in the presence of phentolamine, and, although not commented upon in the paper, relaxation to isoprenaline has been shown to be greater in mesenteric arteries constricted with noradrenaline than with K + (Graves & Poston, 1993).We have also found that endothelium-dependent relaxation is greater following constriction with phenylephrine as compared to PGF 2a or KPSS (Peng et al, 1996). These results imply that a-adrenoceptor stimulation might potentiate NO-mediated relaxation, although the mechanism remains to be elucidated.…”
Section: Discussionsupporting
confidence: 53%
“…It was noticeable that in small arteries the maximum relaxation to isoprenaline was signi®cantly less in the presence of phentolamine, and, although not commented upon in the paper, relaxation to isoprenaline has been shown to be greater in mesenteric arteries constricted with noradrenaline than with K + (Graves & Poston, 1993).We have also found that endothelium-dependent relaxation is greater following constriction with phenylephrine as compared to PGF 2a or KPSS (Peng et al, 1996). These results imply that a-adrenoceptor stimulation might potentiate NO-mediated relaxation, although the mechanism remains to be elucidated.…”
Section: Discussionsupporting
confidence: 53%
“…25,39 It has been shown to exert relaxant effects on vascular smooth muscle because of multiple actions such as affecting cellular Ca 2 þ homeostasis as a nonspecific calcium antagonist, enhancing NO synthesis or inhibiting the activity of phosphodiesterase leading to the subsequent enhancement of cAMP concentration. [40][41][42][43] This study was determined to explore its mechanism underlying the relaxatory actions of chuanxiongzine on corpus cavernosal smooth muscle. Our studies have shown that chuanxiongzine was effective in relaxing isolated rabbit cavernosal strips and depressing the response to PE in a concentration-dependent manner in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments are required before this can be clari®ed, and indeed whether the lack of response in mesenteric arteries is common to other systemic artery types. It is notable that relaxation to another agent that increases cyclic AMP, the putative cyclic AMP speci®c PDE inhibitor tetramethylpyrazine (Lin et al, 1993), is also partially selective in the rat to pulmonary relative to mesenteric arteries (Peng et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Plane & Garland, 1996), and it has been suggested that stimulation of a 1 -adrenoceptors may potentiate relaxation to b-adrenoceptor agonists in pulmonary arteries (Peng et al, 1996;Priest et al, 1997). This could have functional signi®cance, as sympathetic stimulation causes changes in pulmonary vascular resistance that are mediated via noradrenaline and a-and b-adrenoceptors (Hyman et al, 1990).…”
Section: Introductionmentioning
confidence: 99%